PENGARUH BRAND AMBASADOR NCT DREAM DAN EWOM (ELECTRONIC WORD OF MOUTH) TERHADAP MINAT BELI PRODUK SOMETHINC - Hasanah, Yulia Nur; Kusuma, Nadia Farah Putri (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This research was conducted to find out how much influence the use of brand ambassadors has on Somethink products. In addition, this study also aims to determine the effect of Electronic Word Of Mouth so that it can generate consumer buying interest in Something products. What will later be known is whether these three variables have an impact on whether the use of the NCT DREAM brand ambassador can affect consumer buying interest in skincare products Something. This study uses a quantitative method with a descriptive research type and uses a Likert scale as a measurement. The sampling was carried out using the side non-probability method with a total of 100 respondents. The analysis technique used in this study is descriptive and multiple linear regression analysis processed using SPSS. Based on the results of the descriptive analysis in this study, it can be concluded that the respondents' responses obtained through questionnaires to the brand ambassador, electronic word of mouth and purchase intention variables have a percentage that is in the very good category. Based on the results of this study, brand ambassadors and electronic word of mouth simultaneously have a significant effect on the intention to buy skincare products Something